DOES ONE SIZE FIT ALL? EXPLORING ASYNCHRONOUS LEARNING IN A MULTICULTURAL ENVIRONMENT - Morse, Ken (Online Learning, 2003)
Computer-mediated classrooms coupled with heightened emphasis on removing geographic limitations have led to growing dependence on asynchronous learning networks as a delivery medium. An increasingly robust body of literature suggests both positive and negative implications of knowledge delivery using this medium. However, much less is known about the implications of this delivery method relative to the cultural differences which exist in a geographically limitless environment. Exploratory research from a graduate level course was used to ascertain some of the basic cross cultural issues which may be relevant in this environment. Using cultural context as a separator, twenty four participants evenly split between low context participants and high context participants were polled regarding their experience in the course. The poll addressed a number of key issues finding increasing frequency in the asynchronous learning network literature. Results confirm some of the published benefits as touted in the literature, but identify an additional set of issues for further research and evaluation.